Angel eyes - Parker, Robert B., 1932-2010; Atkins, Ace (Parker, Robert B., 1932-2010. Spenser novel., 2019)
"In the latest thriller featuring the legendary Boston PI, Spenser heads to the City of Angels to meet old friends and new enemies in a baffling missing person case that might shake Tinseltown to its core"--